Development of Dinamic Fluid Learning Video Based on Contextual in Water Area for High School Students - Saparini Saparini; Ketang Wiyono; Ahmad Bukhori Muslim (Universitas Lambung Mangkurat, 2020)
The research aims to develop a fluid dynamic learning video-based contextual in water areas that valid and practical. This research is a development study using the Rowntree model, which consists of planning, development, and evaluation stages. The evaluation phase uses the Tessmer evaluation only to the small group evaluation stage. The one to one and small group evaluation stages will be carried out at SMA Negeri 1 Air Saleh in the even semester 2018/2019. Data collected through a walkthrough and questionnaire. The data is then analyzed by determining the mean percentage then converted to get the conclusion of validity and practicality of the video developed. The research conducted concluded that a fluid dynamic learning video-based contextual in water areas have been successfully developed with a percentage of 94% and very practical with a percentage of 87%, making it feasible to use. The product developed can then be used by the teacher to teach the concept of dynamic fluid, especially in schools in water areas, so that students can understand the concept of dynamic fluid based on the surrounding environment.